Diseño de prototipo del myRIO demobox para la demostración de las cualidades y características del dispositivo desarrollado por National Instruments - Sandí-Fonseca, Ignacio Alejandro (Instituto Tecnológico de Costa Rica, 2014)
National Instruments has been known for being a company that equips scientists and engineers with the necessary software and hardware tools to help improve and advance the development of new technologies in a faster and more efficient way. Thanks to this approach is that the NI myRIO has been developed, a device which is geared to students in their final year of engineering to use it in their final class projects or even in their graduation projects,all of this with the aim of facilitating students to develop applications of greater complexity. Because of the wide variety of fields in which the myRIO can be used it becomes difficult to show its capacities, that is why the necessity of creating a new device or application able to fully show many of these capabilities in a portable way arose. This new application or device had to use the less amount of hardware possible to work, and that is how the myRIO demobox was conceived. The demobox gathers together many of the applications that can be developed using the NI myRIO and shows its applicability in fields such as machine vision, automatic control, embedded systems, mechatronics, etc. This paper details the design of the myRIO demobox since it conception, possible apps to implement and the final design of the first prototype.
Proyecto de Graduación (Licenciatura en Ingeniería en Mecatrónica) Instituto Tecnológico de Costa Rica, Escuela de Ingeniería Electromecánica e Ingeniería Electrónica, 2014.
Keywords: Sensores; DIO; AIO; LabVIEW; PID